The effect of castration towards the microstructure of Hippocampus in Wistar rats - Presanavathy P. Tharmalingam; Nyoman Mangku Karmaya; I Nyoman Gede Wardana (Intisari Sains Medis, 2020)
Background: Male ageing is mostly referred to as the declining of the capacity of a man due to age. Even though the physical changes cause by ageing are noticeable, there are several effects of ageing in a male that are concealed by the physical appearance, such as a lower level of testosterone. This study aims to determine the effect of lower testosterone towards the neuron, neuroglia and vasculature of Hippocampus.Methods: An analytic observational study with two-group posttest-only randomized experiment with treatment was conducted among 10 Wistar rats (Rattus norvegicus). Variables assessed in this study were the number of neurons, neuroglia and vasculature of Hippocampus. Data were analyzed using SPSS version 17 for Windows.Results: The average number of neuron cells of Hippocampus was significantly lower in the treatment group compared with control (p=0.007). The significantly lower in the number of neuroglia and vasculature of Hippocampus was also found in the treatment group compared with the control group (p=0.014 and 0.004, respectively) following castration.Conclusion: Hence, we can conclude that the castration has a significant effect in lowering the level of testosterone, number of neurons, neuroglia and vasculature in the Hippocampus of Wistar rats.